Refractory focal segmental glomerulosclerosis in the adult: complete and sustained remissions of two episodes of nephrotic syndrome after a single dose of rituximab. (25th August 2014) - Marasà, Maddalena; Cravedi, Paolo; Ruggiero, Barbara; Ruggenenti, Piero
Abstract : Rituximab therapy may achieve remission of proteinuria in children or adolescents with refractory focal segmental glomerulosclerosis (FSGS), but its effectiveness in adults is uncertain. We describe the case of a 22-year-old Caucasian woman with refractory FSGS that achieved complete and sustained remission of nephrotic syndrome (NS) with one single 375 mg/m 2 rituximab infusion. At 4 months after complete circulating B-cell depletion, proteinuria declined from 4.5 to 0.27 g/24 h and serum albumin normalised. Rituximab was well tolerated and allowed complete withdrawal of previous immunosuppression with steroids and azathioprine. The patient was in sustained remission up to month 32, when she experienced a relapse. A second infusion of rituximab (375 mg/m 2 ) achieved prompt proteinuria reduction with no additional immunosuppressants. At 48 months after the initial treatment, this patient is in complete remission without any immunosuppression. This case suggests that rituximab, even a single dose, may safely promote NS remission in adults with refractory FSGS.